A construção discursiva da identidade feminina: uma análise dos relatos revelados a partir do movimento da hashtag #exposedfortal - Costa, Renata Priscyla Conceição (2024)
Among the representations of female discourse, feminist discourse boosted the need to understand its social and cultural implications when it comes to promote gender equality and strengthen women's rights. This study aims to answer the following research question: How is female identity discursively constructed in the socio-historical context that gave rise to the #exposedfortal hashtag? This research question allowed us to assume that the construction of female identity, in the narratives linked to the #exposedfortal hashtag, occurs through the socio- historical context of the emergence of the #exposedfortal hashtag. For that reason, our general objective is to analyze the discursive construction of female identity, considering the socio- historical context in which this hashtag emerged. This proposal is based on Critical Discourse Analysis (CDA) approaches, especially the approach proposed by Fairclough (1989, 2001, 2003), which creates connections with decolonial reflections on identity, in light of authors such as Hall (2007) and Ferreira (2009) and the concept of empowerment (Berth, 2018). Furthermore, it incorporates conceptions about life stories according to Bertaux (2010) and the perspective of autobiographical (re)memoration by Pineau and Le Grand (2012), Maia- Vasconcelos (2003, 2005, 2022); Maia-Vasconcelos, Freitas and Cardoso (2013), Maia- Vasconcelos, Holanda and Braga (2014), Maia-Vasconcelos and Oliveira (2019), Holanda (2020), Freitas (2015), as well as approaches about gender violence through the studies by Segato (2003) and Almeida (2007). The methodological approach adopted in our proposal is the qualitative interpretative research. Our corpus consisted of two posts published by women indexed with the #exposedfortal hashtag on the social network Instagram. Based on this methodological approach, we performed data analysis, resulting in the following conclusions: results suggest that women shaped their narratives considering the conditions of discursive production of the repercussion of #exposedfortal, which allowed the identification of themes such as psychological/moral and sexual violence; women build an identity that moves from the particular to the general, positioning themselves as victims and also as empowered women. These results provide a deeper understanding of the dynamics of self-narratives associated with the #exposedfortal hashtag, highlighting the interconnection between the conditions of discursive production, the themes of gender violence that were used and the construction of female identity in this specific context. Therefore, we understand the importance of contributing to the understanding of the discourses and narratives that shape female identity in the context of the #exposedfortal hashtag in order to promote reflections and transformations that aim to achieve gender equity and to combat violence against women.